A new species of Notogynaphallia (Platyhelminthes, Geoplanidae) extends the known distribution of land planarians in Chacoan province (Chacoan subregion), South America - Negrete, Lisandro Héctor Luis (2015)
Background: The subfamily Geoplaninae (Geoplanidae) includes land planarian species of the Neotropical Region. In Argentina, the knowledge about land planarian diversity is still incipient, although this has recently increased mainly in the Atlantic Forest ecosystem. However, other regions like Chacoan forests remain virtually unexplored. Results: In this paper, we describe a new species of the genus Notogynaphallia of the Chacoan subregion. This species is characterized by a black pigmentation on the dorsum and a dark grey ventral surface. The eyes with clear halos extend to the dorsal surface. The pharynx is cylindrical. The main features of the reproductive system involve testes anterior to the ovaries, prostatic vesicle intrabulbar (with a tubular proximal portion and a globose distal portion) opening broadly in a richly folded male atrium, common glandular ovovitelline duct and female genital canal dorso-anteriorly flexed constituting a “C”, female atrium tubular proximally and widening distally. Conclusions: This is the first report of the genus Notogynaphallia in Argentina (Chacoan subregion, Neotropical Region) which increases its geographic distribution in South America. Also, as a consequence of features observed in species of the genus, we propose an emendation of the generic diagnosis.